Pharmacological control of diabetes and hypertension comorbidity in the elderly: A study of “real world” data - Foguet-Boreu, Quintí (A pilot randomized controlled trial examining the feasibility, acceptability, and efficacy of Adapted Motivational Interviewing for post-operative bariatric surgery patients, 2017)
• Real world data should be considered in developing Clinical Practice Guidelines. • Some of the drug combinations were associated with better control of diabetes and hypertension than others in the elderly population. • The effort to control diabetes and hypertension comorbidity would benefit from improved adherence to diabetes treatment.